Behavior Model of Buying Decision-making Shoes for the Health of Thai Consumers - Chaiyasong, Chaiyant (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Health care is an increasingly popular trend. Especially foot health is something that is getting attention nowadays. It is an important organ that plays an important role in supporting all the weight of the body as well as cushioning the impact of various activities in daily life that may cause health problems If the health care products are not taken care of like other organs of the body, this article aims to present the behavioral patterns and decision-making in purchasing healthy shoes among Thai consumers. Methodology: This study used document analysis and related research methods. Analyze the content and present it descriptively according to the study objectives. Results: The behavior patterns and decision to buy health shoes of consumers in Thailand There is a pattern of behavior in using healthy shoes among consumers in Thailand. By focusing on brands with a long history There is a unique product that stands out and is different. There is a variety of products, respectively. In addition, consumers have the decision to buy health shoes of consumers in Thailand, namely brands, properties, usage patterns, prices, and distribution locations, respectively. However, an important factor that drives consumers’ decision to buy health shoes in Thailand is the actual results obtained from the reviews of consumers who have used them before. However, it can be said that the results of the above study can be applied to create a brand image of healthy shoes to match the image that consumers have in mind or to improve the perception of the real brand image clearly in the healthy footwear market in the future. Conclusion: The consumer choices in the Thai health shoe market are driven by a preference for well-established brands with distinct identities and varied product offerings. Decision-making factors encompass brand reputation, product features, usage patterns, pricing, and distribution channels, with real user experiences playing a pivotal role. To shape the future health shoe market, creating an authentic brand image that aligns with consumer perceptions is crucial for fostering consumer trust and satisfaction.